Safety and cost of drug‐induced sleep endoscopy outside the operating room. (25th November 2019) - Bergeron, Mathieu; Lee, David R.; DeMarcantonio, Michael A.; Kandil, Ali; Mahmoud, Mohamed A.; Fleck, Robert J.; Ishman, Stacey L.
Abstract : Introduction: Drug‐induced sleep endoscopy (DISE) is used to assess site of obstruction for patients in a pharmacologically induced sleep‐like state. It is traditionally performed in the operating room (OR), however, no data exists regarding the feasibility of this intervention outside the OR in children. The objective is to compare the safety of DISE performed in the MRI induction room to those performed in the OR. Methods: Prospective case‐series of patients undergoing DISE in the MRI induction room (study group) to those assessed in the OR (controls) in a single‐institution pediatric tertiary care center. Consecutive patients undergoing DISE examination for persistent obstructive sleep apnea (OSA) after adenotonsillectomy from September 2016 to September 2017 were included. Results: Overall, 118 patients (38 study patients, 80 controls) with a mean age of 10.6 years (95% confidence interval [CI], 9.3–11.9) underwent DISE; 39.8% (47/118) were female. The most frequent comorbidity was cardiac disease (22.0%, 26/118). The mean obstructive apnea‐hypopnea index was 12.2 events/hour (95% CI, 8.8–15.6) for controls and 13.5 events/hour (95% CI, 8.7–18.3) for study patients ( P = .76). No major complication or unplanned admissions occurred in either group. Induction time was similar (12 vs. 13 minutes, P = .7) as was total procedure time (12 vs. 14 minutes, P = .3) for procedures performed in both settings. Conclusion: There were no significant complications for DISE performed in the OR or the MRI induction room and procedure times were similar. Further assessment of patient outcomes and resource utilization is needed. Level of Evidence: 4 Laryngoscope, 130: 2076–2080, 2020